LAT-1 activity of meta-substituted phenylalanine and tyrosine analogs. Issue 11 (1st June 2016) - Augustyn, Evan; Finke, Karissa; Zur, Arik A.; Hansen, Logan; Heeren, Nathan; Chien, Huan-Chieh; Lin, Lawrence; Giacomini, Kathleen M.; Colas, Claire; Schlessinger, Avner; Thomas, Allen A.
Graphical abstract: Abstract: The transporter protein Large-neutral Amino Acid Transporter 1 (LAT-1, SLC7A5) is responsible for transporting amino acids such as tyrosine and phenylalanine as well as thyroid hormones, and it has been exploited as a drug delivery mechanism. Recently its role in cancer has become increasingly appreciated, as it has been found to be up-regulated in many different tumor types, and its expression levels have been correlated with prognosis. Substitution at the meta position of aromatic amino acids has been reported to increase affinity for LAT-1; however, the SAR for this position has not previously been explored. Guided by newly refined computational models of the binding site, we hypothesized that groups capable of filling a hydrophobic pocket would increase binding to LAT-1, resulting in improved substrates relative to parent amino acid. Tyrosine and phenylalanine analogs substituted at the meta position with halogens, alkyl and aryl groups were synthesized and tested in cis -inhibition and trans -stimulation cell assays to determine activity. Contrary to our initial hypothesis we found that lipophilicity was correlated with diminished substrate activity and increased inhibition of the transporter. The synthesis and SAR of meta -substituted phenylalanine and tyrosine analogs is described.